Dimensionamento de um sistema híbrido eólico-fotovoltaico com armazenamento em baterias e/ou hidrogênio para bombeamento de água - Cruz, Igor Souza (2023)
The present study aimed at optimizing the sizing of a hybrid solar-wind system with battery and/or hydrogen storage for water pumping. Two distinct cases were considered, both being pumping stations, one in the metropolitan region of Fortaleza, with a daily demand of 3716 kWh, and another in Pacatuba with a daily demand of 81758 kWh. The state of the art identified the potential of hybrid generation systems and their application possibilities, mainly related to water pumping. The methodology employed included the simulation the hybrid systems in different pumping demand scenarios using HOMER Pro software. Additionally, the influence of wind and solar intermittency was analyzed, as well as the impact of storage on plant reliability. Finally, the study aimed to identify the best technical and financial scenario for the hybrid plant designed for water pumping. The results indicated that, for both studied locations, the optimal system consisted of a hybrid solar-wind generation with battery storage, composed of photovoltaic modules, wind turbines, lithium batteries, and inverters. Meanwhile, green hydrogen as secondary storage did not provide the best financial solution. The optimal costs found per kilowatt-hour (kWh) were 1.32 US$/kWh for EEA Bairro Aldeota and 1.95 US$/kWh for ETA Gavião.